1989
DOI: 10.1007/bf01788970
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of schizophrenic patients, non-psychotic patients and the general population in a case register area

Abstract: This preliminary study attempts to evaluate the effect of a community psychiatric service on residential mobility by comparing a cohort of schizophrenic patients over a 5-year period with that of non-psychotic and general population control groups in South Verona, a case register area in Northern Italy. No significant differences were found between the groups for different types of movement (within South Verona/outside catchment area of South Verona/outside City of Verona), except for movements within South Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…There are several possible conditions that could result in non-detection of potential cases of schizophrenia during the study period such as: people consulting at CLSCs (for algorithm 4 only), people who did not need the services for a long period of time (10 years), patients who used services for other reasons without being diagnosed with schizophrenia, patients with a misclassification of the disease, people who left the country. Few studies examining the risk of migration in people with a diagnosis of schizophrenia exist, but those run with administrative databases in public managed care system like Italy, showed a similar migration of people with schizophrenia compared to people with non-psychotic disorders or no disorders [47]. In Quebec, the interprovincial mobility is very low (less than 5%) [48].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…There are several possible conditions that could result in non-detection of potential cases of schizophrenia during the study period such as: people consulting at CLSCs (for algorithm 4 only), people who did not need the services for a long period of time (10 years), patients who used services for other reasons without being diagnosed with schizophrenia, patients with a misclassification of the disease, people who left the country. Few studies examining the risk of migration in people with a diagnosis of schizophrenia exist, but those run with administrative databases in public managed care system like Italy, showed a similar migration of people with schizophrenia compared to people with non-psychotic disorders or no disorders [47]. In Quebec, the interprovincial mobility is very low (less than 5%) [48].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This was significantly lower than the national mobility rate of 20% over this time period. While Lesage and Tansella (1989) found no significant differences among their study cohorts in urban to rural migration, McNaught et al (1997) noted that the persons with SMI were more likely to move into inner city areas than out of them.…”
mentioning
confidence: 90%
“…Two studies found the residential mobility of a cohort diagnosed with schizophrenia was either not significantly different from that of the general population (Lesage & Tansella, 1989;McNaught et al, 1997), or was significantly lower than that of a cohort of individuals with non-psychotic disorders (Lesage & Tansella, 1989). Chesteen, Bergeron, and Addison (1970) found that only 4% of their psychiatric patient sample moved an average of once a year, while 8% moved an average of once every 2 years.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Although the drift hypothesis was first described by Lapouse et al (1956) and later by Freeman (1994), no population-based studies investigated whether persons with schizophrenia migrated towards larger cities more often than healthy controls due to the development of the disorder (Lesage and Tansella, 1989). If persons with schizophrenia more often migrate towards urban areas than healthy controls, previous studies reporting urban-rural differences in the prevalence of schizophrenia present upward biased estimates, whereas studies reporting urban-rural differences in the incidence rate of schizophrenia will have no such bias.…”
Section: Introductionmentioning
confidence: 98%